Suspension of cerium oxide particles
By adding specific carboxylic acids to the cerium compound suspension and performing mechanical treatment, an oxygen-containing cerium compound particle suspension with excellent stability and high specific surface area is solved, and the problem of insufficient stability of the cerium compound suspension in the prior art is solved. Improves its performance in catalyst preparation.
Patent Information
- Application Number
- CN202380047705.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-17
- Filing Date
- 2023-06-16
- Publication Date
- 2025-02-11
AI Technical Summary
The existing cerium compound suspensions are insufficient in catalytic applications, especially when pH changes, which affect their catalytic performance.
By providing cerium oxygen-containing compound particles in a liquid medium, combining carboxylic acids of 3 to 9 carbon atoms and functionalized carboxylic acids of 2 carbon atoms, mechanical treatment is performed to form a suspension with excellent stability and high specific surface area.
The excellent stability of the suspension particle size at alkaline pH is achieved, which enhances its application value in catalyst preparation and reduces the risk of workers' exposure to dust.
Smart Images

Figure BDA0005192298850000191
Abstract
Description
[0001] This application claims priority from European patent application EP 22305883.5 filed on June 17, 2022, the entire contents of which are incorporated herein by reference for all purposes. Technical Field
[0002] The present invention relates to a suspension of oxygen-containing cerium compound particles, which suspension can be used in particular for the preparation of a catalyst, and to a method for producing the suspension. Prior art
[0003] Suspensions of cerium compounds have many applications, especially heterogeneous catalysis, especially treating exhaust gases from internal combustion engines. In this case, the catalyst reduces the amount of pollutants emitted from the combustion of the internal combustion fuel, namely carbon monoxide (CO), hydrocarbons (HC), nitrogen oxides (NOx) and particulate matter (PM).
[0004] The suspension of cerium compound can be particularly relevant to the preparation of so-called three-way catalyst or gasoline particulate filter for stoichiometric gasoline or gaseous fuel engine.Cerium compound is an oxygen buffer promoting the conversion of CO, HC and NOx near the stoichiometric ratio.The suspension of cerium compound can also be used for adding some cerium compounds to the formulation of catalyst for lean (lean) engine such as diesel engine or lean-burn gasoline engine.Those lean catalysts can be oxidation catalysts, particulate filter and NOx reduction catalyst (NOx storage or ammonia selective catalytic reduction catalyst) as examples.In this case, cerium compound is considered as oxygen enhancer to promote oxidation reaction or is considered as stabilizer to maintain precious metal in small particles.
[0005] These suspensions can also be used as anti-corrosion additives for coatings or as UV absorbers or moisture control additives in cosmetics, or potentially as mechanical polishing ingredients in polishing applications.
[0006] Document US-A-5922330 discloses aqueous colloidal dispersions of cerium compounds, which consist essentially of cerium IV oxide and / or hydrated oxide, which colloidal dispersions have a pH greater than 5 and a conductivity of at most 2 mS / cm and are formed from cerium nitrate starting products. However, the stability and catalytic properties of the dispersions disclosed in this reference are not yet satisfactory.
[0007] Document US-A-7462665 discloses a mixture of an aqueous lacquer and an aqueous colloidal dispersion of a cerium compound, the dispersion exhibiting a pH of at least 7 and comprising an organic acid having at least three acid functions, the third pK of which is at most 10, or a salt of the acid, and aqueous ammonia or an amine. These dispersions do not appear to be suitable for catalytic applications.
[0008] Should the disclosure of any patents, patent applications, and publications incorporated herein by reference conflict with the description of the present application to the extent that it might render a term unclear, the present description shall take precedence.
[0009] The present invention now makes available a suspension of particles of an oxygen-containing cerium compound having good properties in catalytic applications and facilitating use during catalyst preparation, notably showing excellent stability when the pH of the suspension is increased to an alkaline pH. Summary of the invention
[0010] In a first aspect, the present invention relates to a suspension of particles of an oxygen-containing cerium compound in a liquid medium, preferably an aqueous liquid medium, the particles having a D50 of 10 to 200 nm and a D90 of less than 1000 nm as determined by laser particle size analysis, the suspension comprising at least one carboxylic acid containing 3 to 9 carbon atoms, at least one functionalized carboxylic acid having 2 carbon atoms or any mixture thereof.
[0011] In a specific aspect, the oxygen-containing cerium compound particles of the suspension of the present invention have a D10 equal to or greater than 5 nm as determined by laser particle size analysis.
[0012] In a specific aspect, the oxygen-containing cerium compound particles of the suspension of the invention consist of crystallites having a size equal to or less than 30 nm as determined by XRD after calcination in air at 500° C. for 1 hour.
[0013] In another specific aspect, the oxygen-containing cerium compound particles of the solution of the present invention have a BET specific surface area of at least 50 m2 / g after calcination in air at 500°C for 1 hour.
[0014] In a more specific aspect, the oxygen-containing cerium compound particles of the suspension of the present invention have a total pore volume of at least 0.05 ml / g, preferably at least 1 ml / g, more preferably at least 0.15 ml / g after calcination in air at 500°C for 1 hour as measured by nitrogen adsorption.
[0015] In another aspect, the suspension of the invention contains from 10 wt % to 40 wt % of particles of an oxygen-containing cerium compound expressed as CeO 2 , relative to the total weight of the suspension.
[0016] In another aspect, the suspension of the present invention comprises at least one carboxylic acid, wherein the carboxylic acid comprises a dicarboxylic acid or a tricarboxylic acid, preferably citric acid.
[0017] In another aspect, in the suspension of the present invention, the molar ratio of carboxylic acid to oxygen-containing cerium compound is from 0.05 to 1.5.
[0018] In a particular aspect, the liquid medium of the suspension of the invention is an aqueous medium having a pH of 7 or below.
[0019] In yet another aspect, the D50 of the oxygen-containing cerium compound particles of the suspension of the present invention measured at pH 10 increases by less than 30% compared to the D50 of the oxygen-containing cerium compound particles measured at pH 5.
[0020] In another aspect, the present invention relates to the use of a suspension of the invention as described above in various aspects for preparing a catalyst.
[0021] In another aspect, the present invention relates to a catalyst, in particular an automotive exhaust gas depollution catalyst, obtainable by using the suspension of the invention as described above.
[0022] In yet another aspect, the present invention relates to a catalyst, in particular an automotive exhaust gas depollution catalyst, obtained by using the suspension of the invention as described above.
[0023] In another aspect, the invention relates to the use of the suspension according to the invention as a component of an abrasive composition.
[0024] The present invention also relates to a method for producing the suspension according to the invention, comprising:
[0025] (a) providing a first suspension in a liquid medium, the first suspension comprising an oxygen-containing cerium compound and at least one carboxylic acid having 3 to 9 carbon atoms or a functionalized carboxylic acid having 2 carbon atoms
[0026] (b) subjecting the first suspension to a mechanical treatment to provide a suspension according to any one of claims 1 to 10.
[0027] In a more specific aspect of the method, the pH during step (b) is maintained between 4 and 6.
[0028] In another aspect of the method, inert metal oxide beads, particularly zirconium oxide beads, are used to apply the mechanical energy. DETAILED DESCRIPTION
[0029] Therefore, the present invention relates to a suspension of particles of an oxygen-containing cerium compound in a liquid medium, preferably an aqueous liquid medium, wherein the particles have a D50 of 10 to 200 nm and a D90 of less than 1000 nm as determined by laser particle size analysis, and the suspension comprises at least one carboxylic acid containing 3 to 9 carbon atoms, at least one functionalized carboxylic acid having 2 carbon atoms or any mixture thereof.
[0030] It is unexpectedly found that the suspension according to the present invention has excellent stability of its particle size even when the pH of the suspension is increased to a basic value (which may be as high as 10). This allows great flexibility, for example, when the suspension is combined with other components (particularly alkaline solutions or slurries), especially for catalyst manufacturing. For example, some alkaline solutions or suspensions, such as alkaline solutions of noble metals or transition metals, can be added. The flexibility of the suspension is also advantageous when the pH of the suspension is adjusted (for example, by adding ammonia) to change the rheological properties of the suspension, thereby promoting the coating process on the substrate. The use of the suspension according to the present invention can further reduce or avoid workers being exposed to dust. The oxygen-containing cerium compound particles in the suspension can also show high porosity and surface area, which is particularly advantageous in catalyst applications.
[0031] In the suspension according to the invention, the oxygen-containing cerium compound may be suitably selected from oxides, oxyhydroxides and hydroxides of cerium, or mixtures thereof, which may optionally contain one or more dopants.
[0032] The dopant may be selected from the following non-limiting list: any rare earth element other than cerium or zirconium, such as lanthanum, yttrium, neodymium, or praseodymium.
[0033] Preferably, the oxygen-containing cerium compound is cerium oxide. In particular, the oxygen-containing cerium compound comprises cerium (IV) oxide or consists of cerium (IV) oxide. The content of cerium (IV) oxide in the oxygen-containing cerium compound is generally at least 80% mole, in particular at least 90% mole, at least 91% mole, at least 92% mole, at least 93% mole, at least 94% mole, at least 95% mole, at least 96% mole, at least 97% mole, at least 98% mole, at least 99% mole, at least 100% mole.
[0034] Preferably, the oxygen-containing cerium compound according to the present invention is an oxygen-containing cerium compound according to EP-A-1435338 (the content of which is incorporated into the present application by reference).
[0035] According to EP-A-1435338, the oxygen-containing cerium compound is ceric oxide, which is an oxide consisting essentially of cerium oxide and has a carbon content of not less than 30.0 m / s after calcination at 900° C. for 5 hours. 2 / g specific surface area.
[0036] By convention, the content of oxygen-containing cerium compound in the suspension according to the invention is expressed as wt. % CeO2.
[0037] Diameter(D)
[0038] The oxygen-containing cerium compound is in the form of particles exhibiting a D50 between 10 nm and 200 nm. The D50 may more particularly be between 20 nm and 150 nm, more particularly between 30 nm and 140 nm, more particularly between 40 nm and 120 nm.
[0039] In a more specific aspect, the oxygen-containing cerium compound is in the form of particles exhibiting a D50 of between 60 and 120 nm when measured by laser diffraction.
[0040] The oxygen-containing cerium compound particles exhibit a D90 below 1000 nm. The D90 may be more particularly between 50 nm and 1000 nm, more particularly between 50 nm and 800 nm, even more particularly between 50 nm and 500 nm, even more particularly between 50 nm and 400 nm, even more particularly between 50 nm and 300 nm, even more particularly between 60 nm and 300 nm, even more particularly between 70 nm and 400 nm, even more particularly between 80 nm and 300 nm, even more particularly between 90 nm and 200 nm, even more particularly between 100 nm and 200 nm, even more particularly between 110 nm and 200 nm, even more particularly between 120 nm and 200 nm, even more particularly between 130 nm and 200 nm, even more particularly between 140 nm and 200 nm.
[0041] The oxygen-containing cerium compound particles preferably exhibit a D10 of equal to or greater than 5 nm. D10 may be more particularly equal to or greater than 10 nm, even more particularly equal to or greater than 15 nm, even more particularly equal to or greater than 20 nm, even more particularly equal to or greater than 25 nm, even more particularly equal to or greater than 30 nm, even more particularly equal to or greater than 35 nm, even more particularly equal to or greater than 40 nm, even more particularly equal to or greater than 45 nm.
[0042] The oxygen-containing cerium compound particles preferably exhibit a D10 of equal to or less than 150 nm, more particularly equal to or less than 140 nm, more particularly equal to or less than 130 nm, more particularly equal to or less than 120 nm, more particularly equal to or less than 110 nm, more particularly equal to or less than 100 nm.
[0043] D50 corresponds to the median diameter, as conventionally understood in statistics, determined from the volume distribution of the particle sizes obtained by laser diffraction techniques. This value therefore indicates that on the cumulative distribution curve, 50% of the particles have a diameter greater than D50 and 50% of the particles have a diameter less than D50.
[0044] According to the present invention, D10, D50 and D90 are determined by laser diffraction with a Beckman Coulter LS13320 laser diffraction particle size analyzer (Beckman Coulter, Inc.) using standard procedures predefined by the instrument software.
[0045] The Fraunhofer mode ( https: / / www.beckmancoulter.com / wsrportal / techdocs?docname=B05577AB.pdf ). A relative refractive index of 1.6 is used. The method disclosed in the examples can be conveniently used.
[0046] The measurement can optionally be carried out in water in the presence of a dispersant.
[0047] According to the present invention, D10, D50 and D90 as mentioned in the specification and claims refer to D values measured with a Beckman Coulter LS13320 laser diffraction particle size analyzer (unless a specific other method is used (see Example 2)).
[0048] stability
[0049] A particularly preferred feature of the suspension according to the invention is its stability under conditions of increased pH. This stability feature can be tested, for example, by providing an initial suspension according to the invention, adjusting its pH to pH 5, measuring the D50 of particles in a sample thereof, adding a basic compound or solution to the initial suspension so as to achieve a pH increase to pH 10 and measuring the D50 of particles in the basic suspension.
[0050] For the purpose of this test method, the pH increase is achieved by adding the volume of 4N aqueous ammonia solution required to adjust the pH of the suspension to pH 10. The test method is carried out under essentially isothermal conditions, the temperature being maintained at 25°C + / - 5°C.
[0051] pH measurements were performed with a WTW SetTix pH electrode based on a liquid electrolyte reference.
[0052] In the case of this stability test, the "stability factor" (called SF) can be defined by the following formula:
[0053] SF = (D50 at pH 10 - D50 at pH 5) / D50 at pH 5 x 100
[0054] D50 at pH 10 is the D50 in microns measured for a suspension at pH 10. D50 at pH 5 is the D50 in microns measured for a suspension at pH 5. The lower the SF, the higher the suspension stability.
[0055] For example, SF is typically less than 30%, preferably less than 25%, preferably less than 20%, preferably less than 15%, and more preferably less than 10%. SF may be equal to 0 or about 0. When SF is about 0, it is possible that slightly negative values may be obtained due to the standard deviation of the different measurement methods applied.
[0056] The suspensions according to the invention exhibit very good stability of their particle size, which constitutes an advantage for the processing steps in the preparation of the catalyst.
[0057] According to a particular feature of the suspension according to the invention, the stability factor does not show important variations when the suspension according to the invention is kept in a temperature range from 5°C to 50°C.
[0058] Therefore, the variation with respect to the stability factor (SF) within this temperature range is less than 10%, preferably less than 5%.
[0059] The proportion of oxygen-containing cerium
[0060] The proportion of the oxygen-containing cerium compound in the suspension is generally between 10 and 40 wt %, more particularly between 15 and 35 wt %, even more particularly between 20 and 30 %.
[0061] The ratio expressed as a percentage (%) is given by CeO2 The weight of (corresponding to the oxygen-containing cerium compound) is expressed relative to the total weight of the suspension.
[0062] For example, a proportion of 40 wt % of the oxygen-containing cerium compound corresponds to 40 g of CeO 2 per 100 g of the suspension.
[0063] carboxylic acid
[0064] The suspension of the invention further comprises at least one carboxylic acid containing 3 to 9 carbon atoms, at least one functionalized carboxylic acid having 2 carbon atoms or any mixture thereof.
[0065] According to a particular aspect, the suspension also comprises a mixture of carboxylic acids containing 3 to 9 carbon atoms.
[0066] According to a particular aspect, the suspension also contains a mixture of functionalized carboxylic acids having 2 carbon atoms.
[0067] According to a particular aspect, the suspension also comprises a mixture of at least one carboxylic acid containing from 3 to 9 carbon atoms and at least one functionalized carboxylic acid having 2 carbon atoms.
[0068] The carboxylic acid may also contain at least one functional group other than COOH.
[0069] The functional group may be selected, for example, from the group consisting of OH, C═O, anhydride and ester groups.
[0070] According to a particular aspect, the at least one carboxylic acid containing from 3 to 9 carbon atoms of the solution of the invention may suitably be a mono-, di- or tri-carboxylic acid or an alpha-hydroxy-carboxylic acid.
[0071] The carboxylic acid may more particularly have the formula: R1-COOH, wherein R1 is a linear or branched alkyl group containing from 2 to 8, more particularly from 2 to 7 carbon atoms.
[0072] More particularly, the carboxylic acid of the present invention may be selected from the group consisting of propionic acid, butyric acid, caproic acid, malonic acid, succinic acid, glutamic acid, adipic acid, maleic acid and citric acid.
[0073] In the suspension according to the invention, the at least one carboxylic acid preferably comprises a dicarboxylic acid or tricarboxylic acid having 3 to 9 carbon atoms. Citric acid is very particularly preferred.
[0074] In another aspect, the suspension according to the invention comprises at least one functionalized carboxylic acid containing two carbon atoms. According to this aspect, the carboxylic acid is suitably selected from oxalic acid, glycolic acid and glyoxylic acid.
[0075] In a more specific aspect of the present invention, the molar ratio of carboxylic acid to oxygen-containing cerium compound in the suspension is from 0.05 to 1.5, preferably from 0.1 to 1, more preferably from 0.1 to 0.5.
[0076] Aqueous liquid medium
[0077] The suspension of the present invention is in an aqueous liquid medium. The aqueous liquid medium comprises water.
[0078] According to an embodiment, water is the main component of the liquid medium. In a particular aspect of the invention, the aqueous liquid medium is water.
[0079] According to another embodiment, the aqueous liquid medium may contain at least one other liquid that is miscible with water.
[0080] The further liquid may for example be an organic liquid such as an alcohol, an ester or a ketone.The nature and amount of the further liquid should preferably be such that it does not affect the stability of the suspension.
[0081] The weight ratio of water to the other liquid(s) is preferably between 100 / 0 and 80 / 20, more preferably between 100 / 0 and 90 / 10, even more preferably between 100 / 0 and 95 / 5.
[0082] In a specific aspect of the present invention, the liquid medium, in particular the aqueous liquid medium, further comprises the at least one carboxylic acid containing 3 to 9 carbon atoms and / or the at least one functionalized carboxylic acid having 2 carbon atoms.
[0083] Without wishing to be bound by any theory, it is understood that the at least one carboxylic acid containing 3 to 9 carbon atoms and / or the at least one functionalized carboxylic acid having 2 carbon atoms can be present in solution in the aqueous liquid medium and also in a coordinated form on the surface of the oxygen-containing cerium compound particles.
[0084] In an embodiment, the liquid medium comprises a mineral acid, such as in particular nitric acid. The mineral acid will help to adjust the pH and have an additional stabilizing effect.
[0085] The liquid medium may also contain impurities present in the mechanically treated oxygen-containing cerium compound. Impurities may be released during the mechanical treatment.
[0086] In another embodiment, the liquid medium further comprises a base, such as in particular ammonia. The base can be used to adjust the pH to the desired value.
[0087] The pH of the suspension is between 2.0 and 7.0. In a specific aspect, the pH of the suspension is between 3.0 and 6.0, and preferably between 4.0 and 6.0. In a more preferred aspect, the pH is about 5. When referring to a pH value, "about" means that the pH value can vary above or below that value by plus or minus 4%, preferably 2%.
[0088] solid
[0089] According to another aspect, the invention relies on a solid that can be separated from a suspension after calcining the suspension at 500° C. for 1 hour in air.
[0090] This calcination treatment can be carried out by placing the suspension directly in an electric kiln. In one aspect, the temperature of the kiln is then increased by a temperature ramp of 4°C / min. The solid recovered by this treatment consists mainly of particles of the oxygen-containing cerium compound according to the invention.
[0091] Composition of oxygen-containing cerium compound particles in suspension
[0092] The oxygen-containing cerium compound particles in the suspension according to the invention consist of crystallites having a size equal to or smaller than 30 nm.
[0093] Preferably, the crystallite size is equal to or less than 20 nm. More preferably, the crystallite size is equal to or less than 10 nm.
[0094] In a particular aspect of the invention, the particles of the oxygen-containing cerium compound in the suspension according to the invention consist of crystallites having a size equal to or greater than 3 nm.
[0095] According to another aspect of the present invention, the crystallite size is equal to or greater than 5 nm.
[0096] The average size of crystallites as described above is measured by X-ray diffraction (XRD) technology. X-ray powder diffraction pattern is obtained on the X'pertPro MPD powder diffractometer (PANAlytical Company) equipped with Cu Kα (1.5406 angstroms) radiation source and linear detector X Celerator detector. By scanning with 0.017 ° step, counting time is 28s per step, collecting the scattering intensity data of 2θ values from 19 °-85 °. Crystalline phase is identified by matching with the International Diffraction Data Center Powder Diffraction File (ICDD-PDF). The average crystallite size (DXRD) of the sample is measured by the line broadening considering the instrument width by means of Scherrer (Scherrer) equation, and the lattice parameter is estimated by the intensity of the main reflection (111) by the standard cubic index method.
[0097] XRD is typically performed on a solid separated from a suspension as described in the previous paragraph.
[0098] Specific surface area (SSA)
[0099] The oxygen-containing cerium compound particles of the suspension of the present invention exhibit at least 50 m 2 / g, particularly at least 70 m2 / g, more particularly at least 90 m2 / g specific surface area (BET).
[0100] The specific surface area is less than or equal to 250m 2 / g, particularly less than or equal to 200m2 / g, more particularly less than or equal to 170m2 / g 2 / g.
[0101] According to the present invention, the "specific surface area (BET) of the oxygen-containing cerium compound particles" refers to the specific surface area (BET) of the solid separated from the suspension, ie the oxygen-containing cerium compound, in particular cerium oxide.
[0102] The term "specific surface area (BET)" is understood to mean the BET specific surface area determined by nitrogen adsorption.
[0103] The specific surface area is well known to the skilled person and is measured according to the Brunauer-Emmett-Teller method. The theory of this method was originally described in the journal "The Journal of the American Chemical Society, 60, 309 (1938)". More detailed information on the theory can also be found in Chapter 4 of "Powder surface area and porosity", 2nd edition, ISBN 978-94-015-7955-1. The nitrogen adsorption method is disclosed in the standard ASTM D 3663-03 (reapproved in 2008). In practice, the specific surface area (BET) can be determined automatically with the device Flowsorb II 2300 or the device Tristar 3000 from Micromeritics according to the guidelines of the constructor. They can also be determined automatically with a Mountech Macsorb analyzer model I-1220 according to the manufacturer's instructions. Prior to the measurement, the sample is optionally degassed under vacuum by heating at a temperature of up to 300° C. to remove adsorbed volatile substances. More specific conditions can be found in the examples.
[0104] Total pore volume
[0105] The oxygen-containing cerium compound particles used in the suspension according to the invention may also be further characterized by their total pore volume determined by nitrogen porosimetry.
[0106] The total pore volume can be determined after calcining the solid separated from the suspension at 500°C for 1 hour in air, as described above.
[0107] In the suspension according to the invention, the particles of the oxygen-containing cerium compound have a total pore volume determined by nitrogen adsorption of at least 0.05 ml / g, preferably at least 0.1 ml / g, more preferably 0.15 ml / g.
[0108] In the suspension according to the invention, the particles of the oxygen-containing cerium compound have a total pore volume determined by nitrogen adsorption of at most 1.00 ml / g, preferably at most 0.70 ml / g.
[0109] A TRISTAR II 3020 analyzer from Micromeritics was used for determining nitrogen porosity according to the manufacturer's guidelines.
[0110] The Barett, Joyner and Halenda method with the Harkins-Jura law was used for nitrogen porosimetry. The analysis of the results was performed on the desorption curves. Prior to any measurements, the samples were pretreated in a vacuum oven at 300°C for 60 min to remove any physically adsorbed volatiles, as we did for the specific surface area evaluation.
[0111] Method for producing a suspension
[0112] The invention also relates to a method for producing a suspension according to the invention, comprising:
[0113] (a) providing a first suspension in a liquid medium, the first suspension comprising an oxygen-containing cerium compound and at least one carboxylic acid containing 3 to 9 carbon atoms or a functionalized carboxylic acid containing at least 2 carbon atoms; and
[0114] (b) subjecting the first suspension to a mechanical treatment to provide a suspension according to the invention.
[0115] Preferably, the oxygen-containing cerium compound according to the present invention is an oxygen-containing cerium compound according to EP-A-1435338 (the content of which is incorporated into the present application by reference).
[0116] The amounts of the oxygen-containing cerium compound, carboxylic acid and liquid medium applied in step (a) are suitably adjusted to produce a suspension having the desired ratio of oxygen-containing cerium compound and carboxylic acid in the final suspension recovered after step (b), such ratio being as described above.
[0117] The first suspension of the oxygen-containing cerium compound obtained in step (a) undergoes mechanical treatment (step (b)) to reduce the size of the particles. Use a device that provides enough energy / shear to reduce the size of the particles without significantly affecting the specific surface area. It is believed that the particles of the oxygen-containing cerium compound are in the form of aggregates, which are decomposed into primary particles or smaller aggregates of primary particles. If appropriate, impurities contained in the primary particles are released into the liquid medium. In one aspect, the impurities are alkaline impurities, and the pH of the suspension increases during the mechanical treatment.
[0118] In the process according to the invention, the pH of the suspension during step (b) is maintained at 4 to 6, preferably about 5. If appropriate, the pH of the suspension is maintained by adding an acid. In particular, the pH can be maintained by adding a carboxylic acid as described above. More particularly, the pH is maintained by adding the same at least one carboxylic acid used to provide the suspension in step (a).
[0119] The device used for mechanical treatment in step (b) should also provide good mixing to ensure uniform treatment of the dispersion. The device may be a high pressure homogenizer, a wet jet mill, an agitated bead mill, a high shear mixer or an ultrasonic homogenizer.
[0120] High pressure homogenizers (HPH) involve forcing the dispersion through a narrow gap (e.g., a nozzle with a diameter of 0.1-0.2 mm) at high pressures of about 1500 to 4000 bar, and then allowing the dispersion to relax to atmospheric pressure through the nozzle. The dispersion is then subjected to very high shear stresses, cavitation, and turbulence, causing aggregate disaggregation. Shear is caused by the sudden restriction of flow through a restrictive nozzle.
[0121] The technology of the wet jet mill presents some similarities with that of the HPH. In the wet jet mill, the dispersion is compressed in a chamber, usually at 1500 to 2500 bar, and divided into two streams that pass through two corresponding nozzles with a diameter of 0.1-0.2 mm. The dispersion released from the nozzles at atmospheric pressure then forms two liquid jets. When the two nozzles are in an opposing position, the two jets collide with each other at high speed. The collision generates high shear stresses on the particles and causes them to deagglomerate.
[0122] The technology of agitated bead mills is based on the attrition of solids with hard beads that are in contact with the solid and move at high speed. These beads are often made of hard materials, such as inert metal oxides such as zirconium oxide. The beads preferably exhibit a diameter of less than 500 μm, more particularly between 50 and 500 μm, and even more particularly between 200 and 500 μm. The smaller the diameter, the more beads that can be added in contact with the solid; this enables more collisions to be obtained between the beads and the particles of the solid. More details about the technology can be found in the examples. The technician can use the wet grinding conditions disclosed in the examples to obtain the claimed suspension. The agitated bead mill consists of a grinding container containing beads and a device for moving the beads in the container. The device ensures strong movement of the beads in the container. Different agitated bead mills available on the market can be used in the method of the present invention. The technology of agitated beads is conveniently used to prepare the suspension disclosed in the examples.
[0123] Uses of suspensions
[0124] The invention also relates to the use of the suspension according to the invention for preparing a catalyst, in particular an automotive exhaust gas depollution catalyst. The invention also relates to a device (catalytic converter) comprising the depollution catalyst, which is obtainable by using the suspension according to the invention.
[0125] The present invention also relates to the use of the suspension according to the invention as a component of an abrasive composition, for example for the polishing of substrates such as glass or semiconductor substrates. Notably, the suspension according to the invention can be used in a chemical mechanical planarization (CMP) process for polishing semiconductor substrates.
[0126] The following examples are intended to illustrate and not limit the invention.
[0127] Examples
[0128] Example 1: Materials and methods
[0129] Milled suspension
[0130] Depending on the required analysis, the milled suspension was:
[0131] - Used as such for particle size analysis and dynamic light scattering
[0132] - Calcined in an electric kiln at 500 °C (4 °C / min ramp) for 1 hour to obtain the solid fraction that will be used for XRD, SBET and N2 porosimetry.
[0133] Particle size analysis of the suspension by laser diffraction
[0134] A laser particle size analyzer LS13320 from Beckman Coulter was used. A relative refractive index of 1.6 was used.
[0135] Approximately 20 mL of the suspension was placed in a 50 mL beaker. The pH was then adjusted to 5, 8 or 10 by introducing droplets of 4N ammonia water. After sonication of the suspension at 120 W for 5 min in an external US bath, the suspension was placed under mechanical stirring for 5 min. The pH of the Beckman-Coulter bath was also adjusted to the desired pH by using 5N ammonia water. The suspension was then introduced dropwise into the measurement batch until 40% < PIDS < 50 was obtained. When this condition was met, the measurement was carried out.
[0136] Particle size analysis of the suspension by dynamic light scattering (DLS)
[0137] DLS was carried out on a Zetasizer nano ZS from Malvern.
[0138] Five drops of the suspension were added to 80 mL of deionized water. The suspension thus prepared was sonicated in a bath at 120 W for 5 min. Then, one drop of the suspension thus prepared was added to the DLS cell (12.5 x 12.5 x 45 mm). The cell was filled with 2.5 mL of water and analyzed.
[0139] Specific surface area (BET)
[0140] The surface area was determined by N adsorption at liquid N temperature (77 K) on a TRISTAR II 3020 analyzer from McMerritt by the BET flow method (multipoint). The specific surface area was calculated by the well-known Bruno-Emmett-Teller (BET) method. Prior to the measurement, the sample was pretreated in a vacuum oven at 300° C. for 60 min to remove any residual moisture and adsorbed substances.
[0141] Nitrogen porosity
[0142] A TRISTAR II 3020 analyzer from Micromeritics was used for determining nitrogen porosity according to the manufacturer's guidelines.
[0143] The Barrett, Joyner and Hellend (BJH) method with the Huggins-Jura rule was used for nitrogen porosity determination. The analysis of the results was performed on the desorption curves. Before any measurement, the samples were pretreated in a vacuum oven at 300°C for 60 min to remove any physically adsorbed volatile species, as we did for the specific surface area evaluation.
[0144] XRD of recycled powder
[0145] X-ray powder diffraction patterns were obtained on an X'pertPro MPD powder diffractometer (PANalytical) equipped with a Cu Kα (1.5406 angstroms) radiation source and a linear detector X Celerator detector. Scattering intensity data from 2θ values of 19°-85° were collected by scanning at 0.017° steps and counting time of 28 s per step. Crystalline phases were identified by matching with the International Diffraction Data Center Powder Diffraction File (ICDD-PDF). The average crystallite size (DXRD) of the sample was determined by line broadening considering the instrument width by means of the Scherrer equation, and the lattice parameters were estimated by the intensity of the main reflection (111) using the standard cubic index method.
[0146] For the following examples 2-4 and comparative examples, the cerium oxide particles used in step (a) were prepared according to the method disclosed in EP 1435338B1. The cerium oxide had a specific surface area of 155 m2 / g after calcination at 700°C for 2 hours in air, and a specific surface area of 83 m2 / g after calcination at 800°C for 2 hours in air. The particle size was a D50 of 4.0 μm and a D90 of 6.6 μm. The crystallite size as determined by XRD was about 8 nm. It was observed that the crystallite size of the cerium oxide remained substantially the same after mechanical treatment.
[0147] For Example 5 below, the cerium oxide particles used in step (a) were prepared in the same manner as the cerium oxide particles of Examples 2 to 4, except that the product was spray dried and not calcined in air.
[0148] Example 2
[0149] (40 g) of the cerium oxide prepared above was added to (158 g) of distilled water under mechanical stirring. The pH of the suspension was 6.6. Then (8,9 g) of citric acid was added, resulting in a citric acid / Ce oxide ratio of 0.2. The suspension was further homogenized under mechanical stirring for 15 minutes.
[0150] Then, 150 mL of the homogeneous dispersion was placed in the bowl of a laboratory bead mill (500 ml capacity, bowl diameter 10 cm) containing zirconium oxide beads (605.5 g; average size 350 μm). The dispersion was ground in the bowl with a bead stirrer at 1500 rpm for 60 minutes and finally the pH was raised to pH 5 with the addition of 7.9 mL of 4N NH4OH solution.
[0151] The characteristics of the suspension after grinding are reported in Table 1.
[0152] The concentration of the suspension obtained was 20 wt% ceria. The particle size of the suspension was measured by laser diffraction, with a D50 of 63 nm. When the particle size was measured by another method (by diffuse light scattering (DLS)), the D50 was also high, with a value of 133 nm.
[0153] NH4OH 4N solution was then added to the suspension to raise the pH from 5 to 10. Table 1 shows that there was no effect on the particle size and that the stabilization factor SF was equal to zero.
[0154] Example 3
[0155] Example 3 was carried out following the protocol of Example 2, except that the solids content of the suspension was 25 wt%.
[0156] As can be seen in Table I, the D50 of 61 nm is comparable to that of Example 2 and the concentration effect does not negatively affect the stability of the suspension. At pH 10, the particle size (D50 = 61 nm) remains very stable with a "Stability Factor" (SF) of zero.
[0157] Example 4
[0158] Example 4 follows the protocol of Example 2, except that the solid content of the suspension is 33 wt% instead of 20 wt% and 14,7 g of citric acid solution are added to the initial suspension of cerium oxide. The final pH of the solution is 1.9. Grinding is carried out under these conditions and, finally, the pH is raised to pH 5 by adding 4N NH4OH solution.
[0159] The characteristics of the resulting suspension are reported in Table 1: Similar to Examples 2 and 3, the particle size does not change when the pH is increased to 10 (D50 is 62 nm at pH 5 and pH 10), and therefore SF is equal to zero.
[0160] Example 5:
[0161] Example 4 was carried out following the protocol of Example 1, but the solids content of the suspension was 30 wt% and different zirconium oxide beads were used having an average particle size of 105 μm.
[0162] The characteristics of the produced suspension are reported in Table 1: D50 at pH 5 is 120 nm and we observe a slight increase of D50 at pH 10 (127 nm), but SF remains very low at 5,8%.
[0163] Comparative Example 1
[0164] The suspension was prepared as in Example 2, but using acetic acid instead of citric acid.
[0165] The particle size of the suspension at pH 5 (ie, D50 of 66 nm) was close to that of Example 2 (ie, D50 of 63 nm), meeting the target.
[0166] We added NH4OH to evaluate the stability of the suspension when the pH was raised from 5 to 10. A large increase in particle size was observed (D50 was 16300 nm at pH 10 compared to 63 in Example 2), resulting in a very high stability factor "SF" of more than 20000%.
[0167] Therefore, when the pH increases, the suspension prepared in Comparative Example 1 is unstable.
[0168] Comparative Example 2
[0169] A suspension having a solid content of 20 wt % was prepared under the same conditions as in Comparative Example 1, except that the suspension was milled without adding any carboxylic acid and the pH was fixed at 8 by adding 4N NH 4 OH before starting the milling.
[0170] Table 1 shows that the particle size of the suspension after milling is much larger, with a D50 greater than 2000 nm (ie 2060 nm).
[0171] Comparative Example 3
[0172] The suspension was prepared according to patent EP 0208580. The suspension is different because the particle size is much lower, D50 below 10 nm (i.e. 9.4 nm) when measured by laser diffraction or by DLS. The surface area and N2 porosity of the solid fraction recovered under calcination at 500°C / 1 h in air are much smaller than any of the examples according to the invention (13 nm). 2 / g relative to 119, 117, 125 and 117m in Examples 2-5, respectively 2 / g).
[0173] Here, the following Table 1 shows the characteristics of suspensions according to various examples and comparative examples.
[0174]
Claims
1. A suspension of particles of an oxygen-containing cerium compound in a liquid medium, preferably an aqueous liquid medium, the particles having a D50 of 10 to 200 nm and a D90 of less than 1000 nm as determined by laser particle size analysis, the suspension comprising at least one carboxylic acid containing 3 to 9 carbon atoms, or at least one functionalized carboxylic acid having 2 carbon atoms, or any mixture thereof.
2. The suspension according to claim 1, wherein These oxygen-containing cerium compound particles have a D10 equal to or greater than 5 nm as measured by laser particle size analysis.
3. The suspension according to claim 1 or 2, wherein These oxygen-containing cerium compound particles consist of crystallites having a size equal to or less than 30 nm as determined by XRD after calcination in air at 500° C. for 1 hour.
4. The suspension according to any one of claims 1 to 3, wherein These oxygen-containing cerium compound particles have a particle size of at least 50 μm after being calcined in air at 500° C. for 1 hour. 2 / g BET specific surface area.
5. The suspension according to any one of claims 1 to 4, wherein These oxygen-containing cerium compound particles have a total pore volume of at least 0.05 ml / g, preferably at least 0.1 ml / g, more preferably 0.15 ml / g, as measured by nitrogen adsorption after calcination in air at 500°C for 1 hour.
6. The suspension according to any one of claims 1 to 5, containing from 10 wt% to 40 wt% of particles of an oxygen-containing cerium compound expressed as CeO2, relative to the total weight of the suspension.
7. The suspension according to any one of claims 1 to 6, wherein The carboxylic acid comprises a dicarboxylic acid or a tricarboxylic acid, preferably citric acid.
8. The suspension according to any one of claims 1 to 7, wherein The molar ratio of the carboxylic acid to the oxygen-containing cerium compound is 0.05 to 1.
5.
9. The suspension according to any one of claims 1 to 8, wherein The liquid medium is an aqueous medium having a pH of 7 or below.
10. The suspension according to any one of claims 1 to 9, wherein The D50 of these oxygen-containing cerium compound particles measured at pH 10 increases by less than 30% compared to the D50 of the oxygen-containing cerium compound particles measured at pH 5.
11. Use of the suspension according to any one of claims 1 to 10 for preparing a catalyst.
12. A catalyst, in particular an automotive exhaust gas depollution catalyst, obtainable by the use according to claim 11.
13. Use of a suspension according to any one of claims 1 to 10 as a component of an abrasive composition.
14. A method for producing a suspension according to any one of claims 1 to 10, comprising (a) providing a first suspension in a liquid medium, the first suspension comprising an oxygen-containing cerium compound and at least one carboxylic acid having 3 to 9 carbon atoms or a functionalized carboxylic acid having 2 carbon atoms (b) subjecting the first suspension to a mechanical treatment to provide a suspension according to any one of claims 1 to 10.
15. The method according to claim 14, wherein: The pH during step (b) is maintained between 4 and 6.
16. The method according to claim 14 or 15, wherein: Inert metal oxide beads, particularly zirconium oxide beads, are used to apply the mechanical energy.
Citation Information
Patent Citations
Cerium IV compound and method for its preparation
EP0208580A1
Ceric oxide and method for production thereof, and catalyst for exhaust gas clarification
EP1435338A1
Ceric oxide and method for production thereof, and catalyst for exhaust gas clarification
EP1435338B1
High pH colloidal dispersion of a cerium compound, and a process for its preparation
US5922330A
Aqueous paint composition, particularly a lacquer or a varnish and an aqueous colloidal dispersion of cerium
US7462665B2